Climate Change in the Himalayas - Pant, G. B. (Springer International Publishing, 2018)
This book analyzes the issues associated with climate change in the Himalayas. The purpose of choosing the Himalayas as a focus is because it is a particularly fragile mountain system, highly sensitive to climate change impacts, and it contains one of the largest human populations affected by climate change. The book provides extensive data and information regarding the climate history of the Himalayas, and the current effects of climate change on Himalayan weather systems, and on human and animal populations in the region. The book begins with an overview of global climate change with discussions of data trends and international initiatives, then segues into a history of climate changes and weather trends in the Himalayas. Weather systems of the Himalayas, both past and current, are analyzed and detailed through climate models, seasonal observations of weather fronts, and overviews of various climate scenarios. The book then discusses climate change impacts and signatures specific to the Central Himalayan region, where the largest effects of impacts are observed. Readers will discover analysis presented on water resources, meteorological changes, biodiversity, agriculture and human health along with perspectives of management and policy. This book will appeal to researchers studying climate science, climatology, environmental scientists and policymakers.